Perspectives of energy and resource saving based on integration development model of territorial and industrial complexes - Мацевитый, Юрий Михайлович; Соловей, Виктор Васильевич; Васильев, Анатолий Иосифович (Technology audit and production reserves, 2014)
The technique of determining the reserves of energy and resources on the basis of the integration model of functioning of territorial-industrial complexes is considered in the article. The main aim of the work is to develop the methods of integration of energy and material flows enterprises located in territorial and industrial zones, providing rational use of all kinds of resources, reduction of waste and anthropogenic impact on the environment. One way to achieve this aim is a methodology based on intersectoral integration energetic and technological industrial potential, which can be combined in the framework of territorial and industrial complexes. It is proposed a mathematical model for the analysis of reserves of energy and resources in the implementation of technological integration plants located within the territorial and industrial zones, as well as analysis of consumption of resources and waste generation of enterprises. The results can be applied to the fuel and energy complex, machine building enterprises, mining and metallurgical and chemical-technological profile. The proposed technique makes it possible to realize in practice low-waste energy efficiency production for the development of territorial and industrial complexes, provides a reduction in the unit cost of energy and raw materials in 2,2-3,5 times with simultaneous reduction in emissions by 2-3 times.